Red Blood Cell Transfusions Are Not Associated With Incident Complications or Poor Outcomes in Patients With Intracerebral Hemorrhage - Fernanda Carvalho Poyraz; Amelia Boehme; Azzurra Cottarelli; Lisa Eisler; Mitchell S. V. Elkind; Shivani Ghoshal; Sachin Agarwal; Soojin Park; Jan Claassen; E. Sander Connolly; Eldad A. Hod; David J. Roh (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Anemia is associated with poor intracerebral hemorrhage (ICH) outcomes, yet the relationship of red blood cell (RBC) transfusions to ICH complications and functional outcomes remains unclear. We investigated the impact of RBC transfusion on hospital thromboembolic and infectious complications and outcomes in patients with ICH. Methods and Results Consecutive patients with spontaneous ICH enrolled in a single‐center, prospective cohort study from 2009 to 2018 were assessed. Primary analyses assessed relationships of RBC transfusions on incident thromboembolic and infectious complications occurring after the transfusion. Secondary analyses assessed relationships of RBC transfusions with mortality and poor discharge modified Rankin Scale score 4 to 6. Multivariable logistic regression models adjusted for baseline demographics and medical disease severity (Acute Physiology and Chronic Health Evaluation II), and ICH severity (ICH score).Of 587 patients with ICH analyzed, 88 (15%) received at least one RBC transfusion. Patients receiving RBC transfusions had worse medical and ICH severity. Though patients receiving RBC transfusions had more complications at any point during the hospitalization (64.8% versus 35.9%), we found no association between RBC transfusion and incident complications in our regression models (adjusted odds ratio [aOR], 0.71 [95% CI, 0.42–1.20]). After adjusting for disease severity and other relevant covariates, we found no significant association between RBC transfusion and mortality (aOR, 0.87 [95% CI, 0.45–1.66]) or poor discharge modified Rankin Scale score (aOR, 2.45 [95% CI, 0.80–7.61]). Conclusions In our cohort with ICH, RBC transfusions were expectedly given to patients with higher medical and ICH severity. Taking disease severity and timing of transfusions into account, RBC transfusion was not associated with incident hospital complications or poor clinical ICH outcomes.